Modified Plug Repair with Limited Sphincter Sparing Fistulectomy in the Treatment of Complex Anal Fistulas - Köckerling, Ferdinand; von Rosen, Thomas; Jacob, Dietmar (Frontiers in Surgery, 2014)
Purpose: New technical approaches involving biologically derived products have been used to treat complex anal fistulas in order to avoid the risk of fecal incontinence. The least invasive methods involve filling out the fistula tract with fibrin glue or introduction of an anal fistula plug into the fistula canal following thorough curettage. A review shows that the new techniques involving biologically derived products do not confer any significant advantages. Therefore, the question inevitably arises as to whether the combination of a partial or limited fistulectomy, i.e., of the extrasphincteric portion of the fistula, and preservation of the sphincter muscle by repairing the section of the complex anal fistula running through the sphincter muscle and filling it with a fistula plug produces better results. Methods: A modified plug technique was used, in which the extrasphincteric portion of the complex anal fistula was removed by means of a limited fistulectomy and the remaining section of the fistula in the sphincter muscle was repaired using the fistula plug with fixing button. Results: Of the 52 patients with a complex anal fistula, who had undergone surgery using a modified plug repair with limited fistulectomy of the extrasphincteric part of the fistula and use of the fistula plug with fixing button, there are from 40 patients (follow-up rate: 77%) some kind of follow-up informations, after a mean of 19.32 ± 6.9 months. Thirty-two were men and eight were women, with a mean age of 52.97 ± 12.22 years. Surgery was conducted to treat 36 transsphincteric, 1 intersphincteric, and 3 rectovaginal fistulas. In 36 of 40 patients (90%), the complex anal fistulas or rectovaginal fistulas were completely healed without any sign of recurrence. None of these patients complained about continence problems. Conclusion: A modification of the plug repair of complex anal fistulas with limited fistulectomy of the extrasphincteric part of the fistula and use of the plug with fixing button seems to increase the healing rate in comparison to the standard plug technique.